Evaluación del daño genotóxico mediante determinación de micronúcleos en aves de bosque seco - Bustamante Sinche, Alexandra Nohemi (2018)
Abstract:The alteration and damage of genetic material in wild organisms caused by the various anthropogenic activities affect the persistence of their populations and damage the stability of ecosystems. Of these birds are considered good bioindicators of genotoxic effects due to their behavioral characteristics, diversified diet, abundance, use of various habitats and accessibility. Therefore there are several tests that identify genotoxic damage, the micronucleus test being the simplest and most economical, capable of evaluating the sensitivity of organisms to contaminating agents. The micronuclei (MN) are fragments of chromosomes or complete chromosomes, which spontaneously or because of genotoxic agents, remain outside the nucleus during cell division. The objective of this study was to establish the frequency of micronuclei present in erythrocytes of birds from dry forest. Birds that transit in the dry forest of the canton Zapotillo - Province of Loja were analyzed, and three dense, semi-dense and sparse areas were identified. 180 individuals of 16 species were analyzed. Only 3 species showed sufficient sampling to be analyzed between the presence of micronucleus. The micronucleus analysis showed no significant difference type of.